Existence of periodic travelling waves in systems of nonlinear oscillators on 2Dlattice (in Ukrainian) - S. M. Bak (Математичні Студії, 2011)
It is considered the system of differential equations that describes the dynamics of an infinite system of linearly coupled nonlinear oscillators on 2D-lattice. Results on existence of the periodic travelling waves are obtained.